Preparation method of lithium ion battery with double-layer negative electrode and long-life low-temperature starting power supply
By adopting the preparation method of double-layer negative electrode current collector, a gradient lithium-embedded potential structure is formed, which solves the performance attenuation problem of low-temperature starting power lithium-ion batteries in low-temperature environments, and achieves excellent low-temperature high-current pulse performance, rate performance and cycle performance.
Patent Information
- Application Number
- CN202411634126.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-15
- Publication Date
- 2025-02-14
AI Technical Summary
The existing low-temperature startup power lithium-ion batteries show problems such as degraded rate performance, short cycle life and poor fast charging and circulation performance in low-temperature environments.
By adopting the preparation method of double-layer negative electrode current collector, the first layer of negative electrode slurry and the second layer of negative electrode slurry are applied on the negative electrode sheet respectively to form a gradient lithium-embedded potential structure, and assemble it into a long-life low-temperature starting power supply. Lithium-ion battery.
It significantly improves the high-current pulse performance, rate performance, cycle performance and fast charging and rapid discharge circulation performance of lithium-ion batteries at low temperatures, and improves the first charge and discharge efficiency.
Smart Images

Figure CN119447501A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of preparation of lithium ion battery negative electrode composite materials and low-temperature lithium ion technology, and specifically relates to a preparation method of a double-layer negative electrode and a long-life low-temperature starting power supply lithium ion battery. Background Art
[0002] With the rapid development of new energy in recent years, lithium-ion batteries have been widely used in high-tech fields such as drones, new energy vehicles, and electronic mobile communications. The rate performance, storage life, and cycle performance of lithium-ion batteries can be effectively exerted at room temperature, but their rate performance, storage life, and cycle performance are seriously attenuated under low temperature conditions, especially during low-temperature high-rate charging, where metallic lithium is precipitated on the surface of the negative electrode. As the lithium precipitation phenomenon inside the battery worsens, the battery capacity decays rapidly. At the same time, the generated lithium dendrites can easily cause a short circuit inside the battery, which in turn causes thermal runaway of the battery.
[0003] The invention patent with application number 202211564286.7 discloses a low-temperature lithium-ion battery negative electrode and a lithium-ion battery, wherein the negative electrode coating comprises three layers, the first coating electrode active material is one or more of lithium titanate, niobium titanium oxide, and lithium vanadate, the second coating electrode active material is one or more of silicon, silicon carbon, silicon dioxide, phosphorus, and tin, and the third coating electrode active material is one or two of graphite or hard carbon. The lithium insertion potential of the coating electrode material increases layer by layer from the outer layer to the inner layer to improve the low-temperature performance of the battery, but this method is costly, and it is difficult to control the slurry viscosity and solid content during the mixing process. At the same time, the three coatings will prolong the coating process time, the efficiency is low, and it is difficult to use for industrial production.
[0004] The invention patent with application number 202010182999.1 discloses a method for preparing a multilayer coated current collector in which the active material content gradually decreases and the binder and conductive agent content gradually increase by preparing active material, conductive agent, binder and dispersing solvent in different proportions. The current collector prepared by this method has a gradient distribution of active material, binder and conductive additive from the inside to the outside of the current collector, so as to achieve the purpose of gradually decreasing the porosity of the current collector from the inside to the outside and gradually increasing the electronic conductivity. Although this method can improve the rate performance of the battery to a certain extent, it cannot meet the requirements of large current pulses, and cannot solve the problem of lithium precipitation when the battery is charged and discharged at low temperatures.
[0005] There are several problems with current low-temperature starting power lithium-ion batteries: 1. Insufficient low-temperature starting performance. At -40°C, the lithium ion mobility and electron diffusion rate are reduced, resulting in a decrease in the rate performance of lithium-ion batteries. 2. Short cycle life at low temperatures. During the battery charging and discharging process at low temperatures, the internal impedance increases and the electrochemical performance decays, resulting in a shortened battery life. 3. Poor fast-charging and room-temperature cycle performance. Large current charging and discharging cause the chemical reaction inside the battery cell to be too intense, reducing the lithium ion migration rate and shortening the battery life.
[0006] Therefore, a method for preparing a double-layer negative electrode and a long-life low-temperature starting power lithium-ion battery is needed. Summary of the invention
[0007] The technical problem to be solved by the present invention is to provide a method for preparing a double-layer negative electrode and a long-life low-temperature starting power lithium-ion battery in view of the deficiencies of the above-mentioned prior art. The method forms a double-layer negative electrode current collector by coating the first layer of negative electrode slurry and the second layer of negative electrode slurry on the negative electrode sheet, and then assembles the double-layer negative electrode current collector to form a long-life low-temperature starting power lithium-ion battery. The prepared lithium-ion battery has excellent low-temperature large current pulse performance, low-temperature rate performance, low-temperature cycle performance, excellent room-temperature fast charge and discharge cycle performance, and good first charge and discharge efficiency.
[0008] In order to solve the above technical problems, the technical solution adopted by the present invention is: a method for preparing a double-layer negative electrode and a long-life low-temperature starting power lithium-ion battery, characterized in that the method comprises the following steps:
[0009] Step 1: preparing positive electrode slurry: mixing the positive electrode active material, the conductive agent, the binder and the dispersing solvent evenly to obtain the positive electrode slurry;
[0010] Step 2: preparing the first layer of negative electrode slurry: uniformly mixing the first layer of negative electrode active material, conductive agent, binder and dispersing solvent to obtain the first layer of negative electrode slurry;
[0011] Step 3: preparing the second layer of negative electrode slurry: uniformly mixing the second layer of negative electrode active material, conductive agent, binder and dispersing solvent to obtain the second layer of negative electrode slurry;
[0012] Step 4: preparing the positive electrode current collector: applying the positive electrode slurry obtained in step 1 on the surface of the positive electrode sheet, and then baking to obtain a positive electrode coating on the positive electrode sheet, and then rolling to obtain a positive electrode current collector;
[0013] Step 5, double-layer negative electrode current collector preparation: the first layer of negative electrode slurry obtained in step 2 is coated on the surface of the negative electrode plate, and then baked to obtain a first layer of negative electrode coating on the negative electrode plate, and then the second layer of negative electrode slurry is coated on the first layer of negative electrode coating, and then baked to obtain the second layer of negative electrode coating on the first layer of negative electrode coating, and finally roll-pressed to obtain a double-layer negative electrode current collector;
[0014] Step 6. Preparation of a long-life, low-temperature starting power lithium-ion battery: The double-layer negative electrode collector prepared in step 5, the separator and the positive electrode collector prepared in step 4 are overlapped and assembled in sequence, and the second negative electrode coating of the double-layer negative electrode collector is in contact with the separator, and then mixed with an electrolyte to obtain a long-life, low-temperature starting power lithium-ion battery.
[0015] The present invention obtains positive electrode slurry by uniformly mixing positive electrode active material, conductive agent, adhesive and dispersing solvent. The positive electrode active material plays the role of storing and releasing electric charge in lithium ion battery, and can determine the amount of battery energy. The conductive agent plays the role of collecting microcurrent between active materials and between active materials and current collector, so as to reduce the contact resistance of electrode and accelerate the movement rate of electrons, and can also effectively improve the migration rate of lithium ions in electrode material. The positive electrode slurry has certain viscosity and fluidity by adding adhesive and dispersing solvent, so as to facilitate coating. Then the positive electrode slurry is coated on the surface of aluminum foil, and then baked to shape the positive electrode slurry to obtain positive electrode coating, and then rolled, so as to effectively improve the energy density of lithium ion battery, enhance the surface smoothness, improve the conductivity, enhance the cycle life and safety performance, and obtain positive electrode current collector.
[0016] The first layer of negative electrode active material, conductive agent, adhesive and dispersing solvent are mixed evenly to obtain a first layer of negative electrode slurry, and the second layer of negative electrode active material, conductive agent, adhesive and dispersing solvent are mixed evenly to obtain a second layer of negative electrode slurry. The negative electrode active material plays a role in storing and releasing electrons in the battery, and the two layers cooperate with each other to play a better role. The first layer of negative electrode slurry and the second layer of negative electrode slurry have a certain viscosity and fluidity for easy coating by adding adhesive and dispersing solvent. The first layer of negative electrode slurry obtained in step 2 is coated on the surface of copper foil, and then baked to shape the first layer of negative electrode slurry to obtain a first layer of negative electrode coating, and then coated on the second layer of negative electrode slurry for easy coating, and then baked to shape the second layer of negative electrode slurry to obtain a second layer of negative electrode coating, and finally rolled, so as to effectively improve the energy density of lithium ion batteries, enhance surface smoothness, improve conductivity, enhance cycle life and safety performance, and obtain a double-layer negative electrode current collector;
[0017] A long-life low-temperature starting power lithium-ion battery is obtained by sequentially overlapping and assembling a double-layer negative electrode current collector, a separator and a positive electrode current collector, and combining them with an electrolyte.
[0018] The above-mentioned method for preparing a double-layer negative electrode and a long-life low-temperature starting power supply lithium ion battery is characterized in that the mass ratio of the positive electrode active material, the conductive agent and the adhesive in step one is 94.0-95.4:2.8-3.8:1.8-2.2, the solid content of the positive electrode slurry is 50%-65%, and the viscosity of the positive electrode slurry is 4000mPa·s-6000mPa·s; the positive electrode active material is one or more of nickel-cobalt-manganese ternary material, lithium cobalt oxide and lithium iron phosphate, and the nickel-cobalt-manganese ternary material is NCM111, NCM523, NCM622 or NCM811; the conductive agent is one or more of conductive carbon black, superconducting carbon black, graphene, single-walled carbon nanotubes and multi-walled carbon nanotubes; the adhesive is one or more of polyvinylidene fluoride, polyacrylic acid, styrene-butadiene rubber emulsion and carboxymethyl cellulose mixture, polyacrylonitrile and polyacrylate mixture; the dispersing solvent is N-methylpyrrolidone.
[0019] The above-mentioned method for preparing a double-layer negative electrode and a long-life low-temperature starting power supply lithium-ion battery is characterized in that in step 2, the first layer of negative electrode active material is graphite and / or hard carbon; when the first layer of negative electrode active material is graphite and hard carbon, the mass ratio of the two is 10-30:70-90; the mass ratio of the first layer of negative electrode active material, conductive agent, and adhesive is 93.2:3.5:3.3, the solid content of the first layer of negative electrode slurry is 30%-45%, and the viscosity of the first layer of negative electrode slurry is 2000mPa·s-5000mPa·s; the conductive agent is one or more of conductive carbon black, superconducting carbon black, graphene, single-walled carbon nanotubes and multi-walled carbon nanotubes; the adhesive is one or more of polyvinylidene fluoride, polyacrylic acid, styrene-butadiene rubber emulsion and carboxymethyl cellulose mixture, polyacrylonitrile and polyacrylate mixture; the dispersing solvent is N-methylpyrrolidone and / or deionized water. The present invention can effectively mix graphite and hard carbon materials to enable the battery to have high energy density and high power at the same time, while improving the battery's rate performance, cycle performance and low temperature performance.
[0020] The above-mentioned method for preparing a double-layer negative electrode and a long-life low-temperature starting power supply lithium-ion battery is characterized in that in step three, the second layer of negative electrode active material is one or more of graphite, hard carbon, soft carbon, graphite with a soft carbon-like structure, and hard and soft carbon-coated mesophase carbon microspheres; the mass ratio of the second layer of negative electrode active material, conductive agent, and adhesive is 92.6:3.8:3.6, the solid content of the second layer of negative electrode slurry is 30% to 45%, and the viscosity of the second layer of negative electrode slurry is 2000mPa·s to 4000mPa·s; the conductive agent is one or more of conductive carbon black, superconducting carbon black, graphene, single-walled carbon nanotubes and multi-walled carbon nanotubes; the adhesive is one or more of polyvinylidene fluoride, polyacrylic acid, a mixture of styrene-butadiene rubber emulsion and carboxymethyl cellulose, and a mixture of polyacrylonitrile and polyacrylate; the dispersing solvent is N-methylpyrrolidone and / or deionized water. In the present invention, the second layer of negative electrode active material is selected from one or more of different hard carbons, soft carbons, graphites with soft carbon-like structures, and hard-soft carbon-coated intermediate phase carbon microspheres. Batteries with different functions are prepared according to different application requirements. This is related to the selection of materials, but the double-layer structure can more accurately adjust the battery energy density and power performance compared to the single structure, so that the battery prepared by this method can be suitable for different application scenarios.
[0021] The above-mentioned method for preparing a double-layer negative electrode and a long-life low-temperature starting power supply lithium-ion battery is characterized in that the positive electrode plate in step four is an aluminum foil with a thickness of 12μm to 20μm, and the thickness of the positive electrode collector is 63μm to 67μm.
[0022] The above-mentioned method for preparing a double-layer negative electrode and a long-life low-temperature starting power supply lithium-ion battery is characterized in that the negative electrode plate in step five is a copper foil, a carbon-coated copper foil, a porous copper foil or a PET copper foil with a thickness of 6μm to 15μm, the coating thickness ratio of the first layer of negative electrode slurry and the second layer of negative electrode slurry is 1:1, and the thickness of the double-layer negative electrode current collector is 74μm to 78μm.
[0023] It should be noted that the content of the conductive agent and the binder in the first layer of the negative electrode slurry is smaller than that in the second layer of the negative electrode slurry. This is because the second layer of the negative electrode slurry is farther away from the negative electrode plate than the first layer of the negative electrode slurry, and the electron transmission path is longer. It is necessary to increase the content of the conductive agent and the binder in the slurry to ensure that the double-layer negative electrode collector can provide a stable conductive network, improve the rate performance of the lithium-ion battery, avoid large polarization inside the lithium-ion battery, ensure the excellent low-temperature performance of the lithium-ion battery, and improve the initial charging and discharging efficiency of the lithium-ion battery.
[0024] It should be noted that, by controlling the type, amount and ratio of the first layer of negative electrode active material and the second layer of negative electrode active material, the average lithium insertion potential of the active material in the first layer of negative electrode coating is between 0.3V and 0.8V, and the average lithium insertion potential of the active material in the second layer of negative electrode coating is between 0.1V and 0.2V, so as to ensure that the lithium insertion potential of the double-layer negative electrode current collector gradually increases from the outer layer to the inner layer, forming a gradient lithium insertion potential, so that the high lithium insertion potential of the first layer of negative electrode coating can reduce the lithium precipitation overpotential of the second layer of negative electrode coating, ensure that the lithium metal is prevented from precipitating during the charging and discharging process of the lithium-ion battery at low temperature, improve the cycle performance and safety of the lithium-ion battery at low temperature, and further improve the charging and discharging performance of the lithium-ion battery at low temperature; and the average first charge and discharge efficiency of the first layer of negative electrode coating is 80% to 83%, and the average first charge and discharge efficiency of the second layer of negative electrode coating is 90% to 93%, so that the first charge and discharge efficiency of the active material of the first layer of negative electrode coating is less than the first charge and discharge efficiency of the active material of the second layer of negative electrode coating, and the first charge and discharge efficiency is less than the first charge and discharge efficiency of the active material of the second layer of negative electrode coating. The secondary efficiency gradually increases from the inner layer to the outer layer to form a gradient, which is manifested in the first charge and discharge efficiency of the lithium-ion battery as the average first charge and discharge efficiency of the first layer of the negative electrode coating and the second layer of the negative electrode coating, which improves the first charge and discharge efficiency of the lithium-ion battery, improves the charge and discharge performance of the lithium-ion battery at low temperatures, and makes the active sites of the active material of the first layer of the negative electrode coating greater than the active sites of the active material of the second layer of the negative electrode coating. The active sites gradually increase from the outer layer to the inner layer to form a gradient, which makes the lithium-ion battery more conducive to the rapid deintercalation of lithium ions during large-current fast charge and discharge, improves the low-temperature pulse performance of the battery, reduces the damage of lithium ions to the internal lattice of the negative electrode, and reduces the generation of expansion force in the battery cycle while improving the high-rate charge and discharge performance of the battery. In addition, the porosity of the first layer of the negative electrode coating is smaller than that of the second layer of the negative electrode coating. The gradual increase in porosity can improve the conductivity of the electrode sheet. Since the second layer is far away from the current collector, its conductivity needs to be improved to ensure the consistency of the conductivity of the entire negative electrode sheet in order to effectively play the role of the double-layer negative electrode.
[0025] The above-mentioned method for preparing a double-layer negative electrode and a long-life low-temperature starting power supply lithium-ion battery is characterized in that the thickness of the diaphragm in step six is 12μm to 20μm, and the diaphragm is a polyimide diaphragm, a porous polymer diaphragm, a polyethylene film, a polypropylene film, a cellulose film, a porous polymer film, an aramid film, a polyvinylidene fluoride-hexafluoropropylene copolymer diaphragm, a non-woven fabric film, an inorganic composite film or an aluminum-plastic film.
[0026] The above-mentioned method for preparing a double-layer negative electrode and a long-life low-temperature starting power supply lithium ion battery is characterized in that the electrolyte in step six is prepared by lithium salt and solvent, the concentration of lithium salt in the electrolyte is 1.0 mol / L, and the lithium salt is one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium bisoxalate borate, lithium difluorooxalate borate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethylsulfonyl)imide, and lithium 4,5-dicyano-2-trifluoromethylimidazole; the solvent is one of ethylene carbonate, propylene carbonate, ethylene carbonate, fluoroethylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, γ-butyrolactone, ethyl acetate, propyl acetate, ethyl propionate, propyl propionate, and vinyl sulfate.
[0027] Compared with the prior art, the present invention has the following advantages:
[0028] 1. The present invention forms a double-layer negative electrode current collector by coating a first layer of negative electrode slurry and a second layer of negative electrode slurry on a negative electrode sheet, and then assembles the double-layer negative electrode current collector to form a long-life low-temperature starting power lithium-ion battery, thereby effectively improving the energy density of the lithium-ion battery, enhancing the surface smoothness, improving the conductivity, and enhancing the cycle life and safety performance. The prepared lithium-ion battery has excellent low-temperature large current pulse performance, low-temperature rate performance, low-temperature cycle performance, excellent room-temperature fast charge and discharge cycle performance, and good first charge and discharge efficiency.
[0029] 2. The low-temperature lithium-ion battery prepared by the present invention has excellent low-temperature large-current pulse discharge performance and low-temperature cycle performance even at relatively low temperatures, and the excellent fast-charge, fast-discharge and long-cycle performance at room temperature ensures the service life of the battery. Therefore, the low-temperature battery can exhibit excellent performance in complex low-temperature environments.
[0030] 3. The lithium-ion battery prepared by this method has not only excellent charge and discharge performance and pulse performance at low temperature, but also excellent cycle life. The selected materials are easy to obtain and low in cost. The preparation method is simple and efficient, and is suitable for industrial production applications.
[0031] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 It is a schematic structural diagram of a lithium-ion battery of a medium-long life low-temperature starting power source of the present invention.
[0033] Figure 2 It is a comparison chart of the lithium ion batteries prepared in Example 2 and Example 5 and Comparative Example 1 and Comparative Example 2 of the present invention, discharged at 5C constant current to 2.5V at low temperature test at -40°C.
[0034] Figure 3This is a comparison chart of low temperature pulses of lithium ion batteries prepared in Example 2, Example 5 and Comparative Example 2 of the present invention at -40°C (50C 1s pulse and 25C 30s pulse and then left for 30s) and repeated 3 times.
[0035] Description of reference numerals:
[0036] 1—negative electrode sheet; 2—first layer of negative electrode coating; 3—second layer of negative electrode coating;
[0037] 4—diaphragm; 5—positive electrode coating; 6—positive electrode plate. DETAILED DESCRIPTION
[0038] Figure 1 It is a schematic diagram of the structure of the lithium-ion battery with a long life and low temperature starting power supply of the present invention. Figure 1 It can be seen that the long-life low-temperature starting power lithium-ion battery is composed of a negative electrode sheet 1, a first layer of negative electrode coating 2, a second layer of negative electrode coating 3, a separator 4, a positive electrode coating 5 and a positive electrode sheet 8 from bottom to top.
[0039] Example 1
[0040] This embodiment includes the following steps:
[0041] Step 1: NCM111, superconducting carbon black and carbon nanotube mixture, and polyvinylidene fluoride are uniformly mixed in a mass ratio of 95.4:2.8:1.8, and then N-methylpyrrolidone is added to obtain a positive electrode slurry having a solid content of 50% to 65% and a viscosity of 4000 mPa·s to 6000 mPa·s, which is recorded as A1;
[0042] Step 2: Graphite, superconducting carbon black and carbon nanotube mixture, styrene-butadiene rubber latex and carboxymethyl cellulose mixture are uniformly mixed in a mass ratio of 93.2:3.5:3.3, and then deionized water is added to obtain a first layer of negative electrode slurry with a solid content of 30% to 45% and a viscosity of 2000 mPa·s to 4000 mPa·s, which is recorded as B1;
[0043] Step 3: Evenly mix a mixture of graphite and hard carbon in a mass ratio of 30:70, a mixture of superconducting carbon black and carbon nanotubes, a mixture of styrene-butadiene rubber latex and a mixture of carboxymethyl cellulose in a mass ratio of 93.2:3.5:3.3, and then add deionized water to obtain a first layer of negative electrode slurry having a solid content of 30% to 45% and a viscosity of 3000 mPa·s to 5000 mPa·s, which is recorded as B2;
[0044] Step 4: Evenly mix a mixture of graphite and hard carbon in a mass ratio of 20:80, a mixture of superconducting carbon black and carbon nanotubes, a mixture of styrene-butadiene rubber latex and a mixture of carboxymethyl cellulose in a mass ratio of 93.2:3.5:3.3, and then add deionized water to obtain a first layer of negative electrode slurry having a solid content of 30% to 45% and a viscosity of 3000 mPa·s to 5000 mPa·s, which is recorded as B3;
[0045] Step 5: Evenly mix a mixture of graphite and hard carbon in a mass ratio of 10:90, a mixture of superconducting carbon black and carbon nanotubes, a mixture of styrene-butadiene rubber latex and a mixture of carboxymethyl cellulose in a mass ratio of 93.2:3.5:3.3, and then add deionized water to obtain a first layer of negative electrode slurry having a solid content of 30% to 45% and a viscosity of 3000 mPa·s to 5000 mPa·s, which is recorded as B4;
[0046] Step 6: Evenly mix the soft carbon-like graphite, superconducting carbon black and carbon nanotube mixture, styrene-butadiene rubber latex and carboxymethyl cellulose mixture in a mass ratio of 92.6:3.8:3.6, and then add deionized water to obtain a second layer of negative electrode slurry having a solid content of 35% to 45% and a viscosity of 2000 mPa·s to 4000 mPa·s, which is recorded as C1;
[0047] Step 7, the hard and soft carbon-coated mesophase carbon microspheres, the superconducting carbon black and carbon nanotube mixture, the styrene-butadiene rubber latex and the carboxymethyl cellulose mixture are uniformly mixed in a mass ratio of 92.6:3.8:3.6, and then deionized water is added to obtain a second layer of negative electrode slurry having a solid content of 35% to 45% and a viscosity of 2000 mPa·s to 4000 mPa·s, which is recorded as C2;
[0048] Step 8: Apply the Al obtained in step 1 on the surface of an aluminum foil with a thickness of 17 μm, then bake it to obtain a positive electrode coating on the positive electrode sheet, and then roll-press it to obtain an Al positive electrode current collector with a thickness of 47 μm to 51 μm;
[0049] Step nine, coating the B1, B2, B3, B4, C1, and C2 prepared in steps two to seven on the surfaces of six pieces of 8 μm thick carbon-coated copper foils, baking them, and then rolling them to obtain B1, B2, B3, B4, C1, and C2 negative electrode current collectors with a thickness of 39 μm to 43 μm, respectively;
[0050] Step 10, using the positive electrode collector A1 obtained in step 8 and the negative electrode collectors B1, B2, B3, B4, C1, and C2 obtained in step 9 as the positive electrodes of 7 button batteries, respectively, and using a lithium sheet as the negative electrode, a polyethylene diaphragm with a thickness of 16 μm as the diaphragm, and a low-temperature electrolyte containing 1.0 mol / L lithium hexafluorophosphate of ethylene carbonate (EC), propylene carbonate (PC), fluoroethylene carbonate (FEC), dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), ethyl acetate (EA), ethyl propionate (EP), and propyl propionate (PP) as the electrolyte to prepare 7 button batteries;
[0051] Step 11: Take the button cell made of A1 positive current collector, charge it to 4.2V at 0.1C, leave it for 10min, and then discharge it to 3.0V at 0.1C, record the average charge and discharge voltage and capacity, see Table 1;
[0052] Step 12. Take 6 button batteries made of negative electrode current collectors B1, B2, B3, B4, C1, and C2, discharge them to 0V at 0.1C, then leave them for 10 minutes, and then charge them to 2.5V at 0.1C. Record the average charge and discharge voltage and capacity values, see Table 1.
[0053] Table 1
[0054] Serial number Average charging voltage (V) Average discharge voltage(V) Discharge capacity (mAh / g) A 4.062 / 136 B1 / 0.132 342 B2 / 0.683 295 B3 / 0.518 290 B4 / 0.399 285 C1 / 0.176 280 C2 / 0.164 325
[0055] As can be seen from Table 1, B2, B3 and B4 have high lithium insertion potentials, while C1 and C2 have low lithium insertion potentials (the higher the average discharge voltage, the higher the lithium insertion potential) (the power performance of hard carbon is better than that of graphite, and the energy density of graphite is better than that of hard carbon). The negative electrodes B2, B3 and B4 are respectively used as the first coating of the negative electrode current collector, and C1 or C2 is respectively used as the second coating of the negative electrode current collector to make the negative electrode current collector, and the positive electrode material A is used as the positive electrode current collector.
[0056] The positive electrode active material in this embodiment may also be one or more of a nickel-cobalt-manganese ternary material, lithium cobalt oxide and lithium iron phosphate, and the nickel-cobalt-manganese ternary material is NCM111, NCM523, NCM622 or NCM811;
[0057] The conductive agent in the preparation of the positive electrode slurry, the first layer negative electrode slurry and the second layer negative electrode slurry can also be one or more of conductive carbon black / superconducting carbon black and graphene, single-walled carbon nanotubes and multi-walled carbon nanotubes; the adhesive can also be one or more of polyvinylidene fluoride, polyacrylic acid, a mixture of styrene-butadiene rubber latex and carboxymethyl cellulose, and a mixture of polyacrylonitrile and polyacrylate;
[0058] The dispersion solvent in the preparation of the first layer of negative electrode slurry and the second layer of negative electrode slurry may also be N-methylpyrrolidone and / or deionized water;
[0059] The second layer of negative electrode active material may also be one or more of graphite, hard carbon, soft carbon, graphite with a soft carbon-like structure, and hard-soft carbon-coated mesophase carbon microspheres.
[0060] Example 2
[0061] This embodiment includes the following steps:
[0062] Step 1: coating the Al prepared in Example 1 on the surface of an aluminum foil with a thickness of 16 μm, and then baking to obtain a positive electrode coating on the positive electrode sheet, and then rolling to obtain an Al positive electrode current collector with a thickness of 63 μm to 67 μm;
[0063] Step 2: Apply the B2 prepared in Example 1 on the surface of a carbon-coated copper foil with a thickness of 9 μm, and then bake to obtain a B2 coating on the negative electrode sheet, then apply the C1 prepared in Example 1 with the same thickness on the B2 coating, and then bake to obtain a C1 coating on the B2 coating, and finally roll-press to obtain a B2C1 double-layer negative electrode current collector with a thickness of 74 μm to 78 μm;
[0064] Step 3: The B2C1 double-layer negative electrode collector prepared in step 2, a polyethylene separator with a thickness of 16 μm, and the A1 positive electrode collector prepared in step 1 are sequentially overlapped and assembled, and the second negative electrode coating of the B2C1 double-layer negative electrode collector is in contact with the separator, and then an electrolyte containing 1.0 mol / L lithium hexafluorophosphate of ethylene carbonate (EC), propylene carbonate (PC), fluoroethylene carbonate (FEC), dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), ethyl acetate (EA), ethyl propionate (EP), and propyl propionate (PP) is prepared, and then after standing, formation, exhaustion and volume separation, a B2C1 long-life low-temperature starting power lithium ion battery is obtained.
[0065] In this embodiment, the positive electrode plate can also be an aluminum foil with a thickness of 12 μm or 20 μm;
[0066] In this embodiment, the negative electrode plate can also be a copper foil with a thickness of 6 μm or 15 μm, a carbon-coated copper foil, a porous copper foil or a PET copper foil;
[0067] In this embodiment, the diaphragm may also be a polyimide diaphragm, a porous polymer diaphragm, a polypropylene film, a cellulose film, a porous polymer film, an aramid film, a polyvinylidene fluoride-hexafluoropropylene copolymer diaphragm, a non-woven fabric film, an inorganic composite film or an aluminum-plastic film;
[0068] In this embodiment, the lithium salt may also be one of lithium tetrafluoroborate, lithium dioxalate borate, lithium difluorooxalate borate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethylsulfonyl)imide, and lithium 4,5-dicyano-2-trifluoromethylimidazole;
[0069] In this embodiment, the solvent can also be one or more of ethylene carbonate, propylene carbonate, ethylene carbonate, fluoroethylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, γ-butyrolactone, ethyl acetate, propyl acetate, ethyl propionate, propyl propionate, and vinyl sulfate.
[0070] Example 3
[0071] This embodiment includes the following steps:
[0072] Step 1: coating the Al prepared in Example 1 on the surface of an aluminum foil with a thickness of 16 μm, and then baking to obtain a positive electrode coating on the positive electrode sheet, and then rolling to obtain an Al positive electrode current collector with a thickness of 63 μm to 67 μm;
[0073] Step 2: The B3 prepared in Example 1 is coated on the surface of a carbon-coated copper foil with a thickness of 9 μm, and then baked to obtain a B3 coating on the negative electrode sheet, and then the C1 prepared in Example 1 with the same thickness is coated on the B3 coating, and then baked to obtain a C1 coating on the B3 coating, and finally roll-pressed to obtain a B3C1 double-layer negative electrode current collector with a thickness of 74 μm to 78 μm;
[0074] Step 3: The B3C1 double-layer negative electrode collector prepared in step 2, a polyethylene separator with a thickness of 16 μm, and the A1 positive electrode collector prepared in step 1 are overlapped and assembled in sequence, and the second negative electrode coating of the B3C1 double-layer negative electrode collector is in contact with the separator, and then an electrolyte containing 1.0 mol / L lithium hexafluorophosphate of ethylene carbonate (EC), propylene carbonate (PC), fluoroethylene carbonate (FEC), dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), ethyl acetate (EA), ethyl propionate (EP), and propyl propionate (PP) is prepared, and then after standing, forming, evacuating, and volume separation, a B3C1 long-life low-temperature starting power lithium-ion battery is obtained.
[0075] Example 4
[0076] This embodiment includes the following steps:
[0077] Step 1: coating the Al prepared in Example 1 on the surface of an aluminum foil with a thickness of 16 μm, and then baking to obtain a positive electrode coating on the positive electrode sheet, and then rolling to obtain an Al positive electrode current collector with a thickness of 63 μm to 67 μm;
[0078] Step 2: The B4 prepared in Example 1 is coated on the surface of a carbon-coated copper foil with a thickness of 9 μm, and then baked to obtain a B4 coating on the negative electrode sheet, and then the C1 prepared in Example 1 with the same thickness is coated on the B4 coating, and then baked to obtain a C1 coating on the B4 coating, and finally roll-pressed to obtain a B4C1 double-layer negative electrode current collector with a thickness of 74 μm to 78 μm;
[0079] Step 3: The B4C1 double-layer negative electrode collector prepared in step 2, a polyethylene separator with a thickness of 16 μm, and the A1 positive electrode collector prepared in step 1 are overlapped and assembled in sequence, and the second negative electrode coating of the B4C1 double-layer negative electrode collector is in contact with the separator, and then an electrolyte containing 1.0 mol / L lithium hexafluorophosphate and a mixed solvent of ethylene carbonate (EC), propylene carbonate (PC), fluoroethylene carbonate (FEC), dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), ethyl acetate (EA), ethyl propionate (EP), and propyl propionate (PP) is added, and then after standing, formation, exhaustion and volume separation, a B4C1 long-life low-temperature starting power lithium-ion battery is obtained.
[0080] Example 5
[0081] This embodiment includes the following steps:
[0082] Step 1: coating the Al prepared in Example 1 on the surface of an aluminum foil with a thickness of 16 μm, and then baking to obtain a positive electrode coating on the positive electrode sheet, and then rolling to obtain an Al positive electrode current collector with a thickness of 63 μm to 67 μm;
[0083] Step 2: The B2 prepared in Example 1 is coated on the surface of a carbon-coated copper foil with a thickness of 9 μm, and then baked to obtain a B2 coating on the negative electrode sheet, and then the C2 prepared in Example 1 with the same thickness is coated on the B2 coating, and then baked to obtain a C2 coating on the B2 coating, and finally roll-pressed to obtain a B2C2 double-layer negative electrode current collector with a thickness of 74 μm to 78 μm;
[0084] Step 3: The B2C2 double-layer negative electrode collector prepared in step 2, a polyethylene separator with a thickness of 16 μm, and the A1 positive electrode collector prepared in step 1 are overlapped and assembled in sequence, and the second negative electrode coating of the B2C2 double-layer negative electrode collector is in contact with the separator, and then an electrolyte containing 1.0 mol / L lithium hexafluorophosphate of ethylene carbonate (EC), propylene carbonate (PC), fluoroethylene carbonate (FEC), dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), ethyl acetate (EA), ethyl propionate (EP), and propyl propionate (PP) is prepared, and then after standing, formation, exhaustion and volume separation, a B2C2 long-life low-temperature starting power lithium-ion battery is obtained.
[0085] Example 6
[0086] This embodiment includes the following steps:
[0087] Step 1: coating the Al prepared in Example 1 on the surface of an aluminum foil with a thickness of 16 μm, and then baking to obtain a positive electrode coating on the positive electrode sheet, and then rolling to obtain an Al positive electrode current collector with a thickness of 63 μm to 67 μm;
[0088] Step 2: The B3 prepared in Example 1 is coated on the surface of a carbon-coated copper foil with a thickness of 9 μm, and then baked to obtain a B3 coating on the negative electrode sheet, and then the C2 prepared in Example 1 with the same thickness is coated on the B3 coating, and then baked to obtain a C2 coating on the B3 coating, and finally roll-pressed to obtain a B3C2 double-layer negative electrode current collector with a thickness of 74 μm to 78 μm;
[0089] Step 3: The B3C2 double-layer negative electrode collector prepared in step 2, a polyethylene separator with a thickness of 16 μm, and the A1 positive electrode collector prepared in step 1 are overlapped and assembled in sequence, and the second negative electrode coating of the B3C2 double-layer negative electrode collector is in contact with the separator, and then an electrolyte containing 1.0 mol / L lithium hexafluorophosphate of ethylene carbonate (EC), propylene carbonate (PC), fluoroethylene carbonate (FEC), dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), ethyl acetate (EA), ethyl propionate (EP), and propyl propionate (PP) is prepared, and then after standing, formation, exhaustion and volume separation, a B3C2 long-life low-temperature starting power lithium-ion battery is obtained.
[0090] Example 7
[0091] This embodiment includes the following steps:
[0092] Step 1: coating the Al prepared in Example 1 on the surface of an aluminum foil with a thickness of 16 μm, and then baking to obtain a positive electrode coating on the positive electrode sheet, and then rolling to obtain an Al positive electrode current collector with a thickness of 63 μm to 67 μm;
[0093] Step 2: The B4 prepared in Example 1 is coated on the surface of a carbon-coated copper foil with a thickness of 9 μm, and then baked to obtain a B4 coating on the negative electrode sheet, and then the C2 prepared in Example 1 with the same thickness is coated on the B4 coating, and then baked to obtain a C2 coating on the B4 coating, and finally roll-pressed to obtain a B4C2 double-layer negative electrode current collector with a thickness of 74 μm to 78 μm;
[0094] Step 3: The B4C2 double-layer negative electrode collector prepared in step 2, a polyethylene separator with a thickness of 16 μm, and the A1 positive electrode collector prepared in step 1 are overlapped and assembled in sequence, and the second negative electrode coating of the B4C2 double-layer negative electrode collector is in contact with the separator, and then an electrolyte containing 1.0 mol / L lithium hexafluorophosphate and a mixed solvent of ethylene carbonate (EC), propylene carbonate (PC), fluoroethylene carbonate (FEC), dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), ethyl acetate (EA), ethyl propionate (EP), and propyl propionate (PP) is added, and then after standing, formation, exhaustion and volume separation, a B4C2 long-life low-temperature starting power lithium-ion battery is obtained.
[0095] Comparative Example 1
[0096] This comparative example comprises the following steps:
[0097] Step 1: coating the Al prepared in Example 1 on the surface of an aluminum foil with a thickness of 16 μm, and then baking to obtain a positive electrode coating on the positive electrode sheet, and then rolling to obtain an Al positive electrode current collector with a thickness of 63 μm to 67 μm;
[0098] Step 2: coating the B1 prepared in Example 1 on the surface of a carbon-coated copper foil with a thickness of 9 μm, then baking, and finally rolling to obtain a B1 negative electrode current collector with a thickness of 74 μm to 78 μm;
[0099] Step 3: The B1 negative electrode current collector prepared in step 2, a polyethylene separator with a thickness of 16 μm, and the A1 positive electrode current collector prepared in step 1 are overlapped and assembled in sequence, and then an electrolyte containing 1.0 mol / L lithium hexafluorophosphate and a mixed solvent of ethylene carbonate (EC), propylene carbonate (PC), fluoroethylene carbonate (FEC), dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), ethyl acetate (EA), ethyl propionate (EP), and propyl propionate (PP) is added, and then the electrolyte is allowed to stand, formed, evacuated, and divided to obtain a B1 long-life low-temperature starting power lithium-ion battery.
[0100] Comparative Example 2
[0101] This comparative example comprises the following steps:
[0102] Step 1: coating the Al prepared in Example 1 on the surface of an aluminum foil with a thickness of 16 μm, and then baking to obtain a positive electrode coating on the positive electrode sheet, and then rolling to obtain an Al positive electrode current collector with a thickness of 63 μm to 67 μm;
[0103] Step 2: coating the B2 prepared in Example 1 on the surface of a carbon-coated copper foil with a thickness of 9 μm, then baking, and finally rolling to obtain a B2 negative electrode current collector with a thickness of 74 μm to 78 μm;
[0104] Step 3: The B2 negative electrode current collector prepared in step 2, a polyethylene separator with a thickness of 16 μm, and the A1 positive electrode current collector prepared in step 1 are overlapped and assembled in sequence, and then an electrolyte containing 1.0 mol / L lithium hexafluorophosphate and a mixed solvent of ethylene carbonate (EC), propylene carbonate (PC), fluoroethylene carbonate (FEC), dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), ethyl acetate (EA), ethyl propionate (EP), and propyl propionate (PP) is added, and then the electrolyte is allowed to stand, formed, evacuated, and divided to obtain a B2 long-life, low-temperature starting power lithium-ion battery.
[0105] The lithium ion batteries prepared in Examples 2 to 7 and Comparative Examples 1 to 2 were tested for discharge capacity in grams, internal resistance, and first charge and discharge efficiency. The test results are shown in Table 2.
[0106] Table 2
[0107] Serial number Discharge capacity (mAh / g) Internal resistance(mΩ) First charge and discharge efficiency (%) Example 2 140.5 0.66 84.3 Example 3 137.8 0.68 83.6 Example 4 135.2 0.64 82.2 Example 5 141.4 0.65 84.8 Example 6 138.6 0.67 83.3 Example 7 135.9 0.70 82.4 Comparative Example 1 148.6 0.76 91.2 Comparative Example 2 132.6 0.69 80.3
[0108] As can be seen from Table 2, in Example 2, Example 3, Example 4, Example 5, Example 6, and Example 7, since the negative electrode has a second coating, the material selected for the coating has a higher initial charge and discharge efficiency, which is improved compared to the negative electrode current collector of Comparative Example 2, which only uses the first coating B5; at the same time, the gram capacity is also higher than that of the battery with only the first coating B5. However, the gram capacity and initial charge and discharge efficiency of the double-layer negative electrode are lower than those of the battery with only B1 in the first coating.
[0109] The lithium ion batteries prepared in Examples 2 to 7 and Comparative Examples 1 to 2 were subjected to a low-temperature discharge test at -40°C with a 5C constant current discharge to 2.5V, a pulse test at -40°C (50C 1s pulse and 25C 30s pulse and then left for 10s) and repeated 3 times, and a low-temperature cycle test at -40°C with a current of 1C. The results are shown in Table 3.
[0110] Table 3
[0111]
[0112]
[0113] As can be seen from Table 3, in Example 2, Example 3, Example 4, Example 5, Example 6, and Example 7, the low-temperature performance indicators of the negative electrode are all improved after the second coating is added, especially in Example 5, where the 5C constant current discharge at -40°C can release 80.2% of the capacity, and the minimum inflection point voltage of the pulse repeated 3 times at -40°C (50C1s pulse and 25C30s pulse for 30s) can reach 2.5V, and the low-temperature cycle of charge and discharge with a current of 1C at -40°C reaches 500 weeks, while the low-temperature performance of Comparative Examples 1 and 2 is poor, especially Comparative Example 1 cannot complete the two tests of low-temperature pulse and low-temperature cycle. This is because the negative electrode adopts a double-layer structure to effectively build a conductive network and avoid large polarization inside the battery; the lithium insertion potential is set in a gradient to ensure that lithium metal is prevented from precipitating during the charge and discharge process of the battery at low temperatures, thereby improving the cycle performance and safety of the battery at low temperatures.
[0114] Figure 2 : is a comparison chart of the lithium ion batteries prepared in Example 2, Example 5 and Comparative Example 1, Comparative Example 2 of the present invention, discharged at a constant current of 5C to a low temperature of 2.5V at -40°C. Figure 2 It can be seen that the low temperature capability of Example 5 is better than that of Example 2 and much better than that of Comparative Example 1. It can be inferred that the low temperature performance of the battery prepared by the double-layer structure of the present invention is much better than that of the battery prepared by the graphite negative electrode material, and the hard-soft carbon-coated mesophase carbon microspheres are also better in low temperature performance than the graphite material with a soft carbon structure.
[0115] Figure 3 This is a comparison chart of the low temperature pulses of the lithium ion batteries prepared in Example 2, Example 5 and Comparative Example 2 of the present invention at -40°C (50C 1s pulse and 25C 30s pulse and then left for 30s) and repeated 3 times. Figure 3 It can be seen that the low-temperature pulse performance of Example 5 is better than that of Example 2 and much better than that of Comparative Example 2. It can be inferred that the low-temperature pulse performance of the battery prepared by the double-layer structure of the present invention is much better than that of the battery prepared by the single-layer hard carbon and graphite negative electrode materials, and the hard-soft carbon-coated intermediate phase carbon microspheres also have better low-temperature pulse performance than the graphite material with a soft carbon structure.
[0116] The lithium ion batteries prepared in Examples 2 to 7 and Comparative Examples 1 to 2 were subjected to 55°C 7-day high temperature storage, room temperature storage, and room temperature 5C fast charge cycle tests. The test results are shown in Table 4.
[0117] Table 4
[0118]
[0119] As can be seen from Table 4, in Example 2, Example 3, Example 4, Example 5, Example 6, and Example 7, it can be seen that the storage performance of Examples 2 to 7 is better than that of Comparative Example 2 in the storage at 55°C for 7 days, but worse than that of Comparative Example 1. The same phenomenon is observed in the storage at 25°C for 30 days, which is determined by the structure of the hard carbon material itself. The greater the proportion of hard carbon content in the negative electrode activity, the worse its storage performance. In the room temperature 5C fast charge and discharge cycle test, the cycle performance of Example 2, Example 3, Example 4, Example 5, Example 6, and Example 7 are all better than that of Comparative Example 1 and Comparative Example 2. This is attributed to the structural design of the negative electrode double coating. By regulating the active sites, lithium ions can be quickly deintercalated during high-current fast charge and discharge, thereby reducing the damage of lithium ions to the internal lattice of the negative electrode, thereby improving the high-rate charge and discharge performance of the battery while reducing the expansion generated during the battery cycle.
[0120] Example 8
[0121] The difference between this embodiment and embodiment 2 is that A1 is prepared by uniformly mixing NCM111, a mixture of superconducting carbon black and carbon nanotubes, and polyvinylidene fluoride in a mass ratio of 94.0:3.8:2.2.
[0122] Example 9
[0123] The difference between this embodiment and embodiment 2 is that the A1 is prepared by uniformly mixing NCM111, a mixture of superconducting carbon black and carbon nanotubes, and polyvinylidene fluoride in a mass ratio of 94.5:3.4:2.0.
[0124] The above is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent change made to the above embodiment according to the technical essence of the present invention still falls within the protection scope of the technical solution of the present invention.
Claims
1. A method for preparing a double-layer negative electrode and a long-life low-temperature starting power lithium-ion battery, characterized in that: The method comprises the following steps: Step 1: preparing positive electrode slurry: mixing the positive electrode active material, the conductive agent, the binder and the dispersing solvent evenly to obtain the positive electrode slurry; Step 2: preparing the first layer of negative electrode slurry: uniformly mixing the first layer of negative electrode active material, conductive agent, binder and dispersing solvent to obtain the first layer of negative electrode slurry; Step 3: preparing the second layer of negative electrode slurry: uniformly mixing the second layer of negative electrode active material, conductive agent, binder and dispersing solvent to obtain the second layer of negative electrode slurry; Step 4: preparing the positive electrode current collector: applying the positive electrode slurry obtained in step 1 on the surface of the positive electrode sheet, and then baking to obtain a positive electrode coating on the positive electrode sheet, and then rolling to obtain a positive electrode current collector; Step 5, double-layer negative electrode current collector preparation: the first layer of negative electrode slurry obtained in step 2 is coated on the surface of the negative electrode plate, and then baked to obtain a first layer of negative electrode coating on the negative electrode plate, and then the second layer of negative electrode slurry is coated on the first layer of negative electrode coating, and then baked to obtain the second layer of negative electrode coating on the first layer of negative electrode coating, and finally roll-pressed to obtain a double-layer negative electrode current collector; Step 6. Preparation of a long-life, low-temperature starting power lithium-ion battery: The double-layer negative electrode collector prepared in step 5, the separator and the positive electrode collector prepared in step 4 are overlapped and assembled in sequence, and the second negative electrode coating of the double-layer negative electrode collector is in contact with the separator, and then mixed with an electrolyte to obtain a long-life, low-temperature starting power lithium-ion battery.
2. The method for preparing a double-layer negative electrode and a long-life low-temperature starting power lithium-ion battery according to claim 1, characterized in that: The mass ratio of the positive electrode active material, the conductive agent and the adhesive in step one is 94.0-95.4:2.8-3.8:1.8-2.2, the solid content of the positive electrode slurry is 50%-65%, and the viscosity of the positive electrode slurry is 4000mPa·s-6000mPa·s; the positive electrode active material is one or more of nickel-cobalt-manganese ternary material, lithium cobalt oxide and lithium iron phosphate, and the nickel-cobalt-manganese ternary material is NCM111, NCM523, NCM622 or NCM811; the conductive agent is one or more of conductive carbon black, superconducting carbon black, graphene, single-walled carbon nanotubes and multi-walled carbon nanotubes; the adhesive is one or more of polyvinylidene fluoride, polyacrylic acid, styrene-butadiene rubber emulsion and carboxymethyl cellulose mixture, polyacrylonitrile and polyacrylate mixture; the dispersing solvent is N-methylpyrrolidone.
3. The method for preparing a double-layer negative electrode and a long-life low-temperature starting power lithium-ion battery according to claim 1, characterized in that: In step 2, the first layer of negative electrode active material is graphite and / or hard carbon; when the first layer of negative electrode active material is graphite and hard carbon, the mass ratio of the two is 10-30:70-90; the mass ratio of the first layer of negative electrode active material, conductive agent, and adhesive is 93.2:3.5:3.3, the solid content of the first layer of negative electrode slurry is 30%-45%, and the viscosity of the first layer of negative electrode slurry is 2000mPa·s-5000mPa·s; the conductive agent is one or more of conductive carbon black, superconducting carbon black, graphene, single-walled carbon nanotubes and multi-walled carbon nanotubes; the adhesive is one or more of polyvinylidene fluoride, polyacrylic acid, styrene-butadiene rubber emulsion and carboxymethyl cellulose mixture, polyacrylonitrile and polyacrylate mixture; the dispersing solvent is N-methylpyrrolidone and / or deionized water.
4. The method for preparing a double-layer negative electrode and a long-life low-temperature starting power lithium-ion battery according to claim 1, characterized in that: In step three, the second layer of negative electrode active material is one or more of graphite, hard carbon, soft carbon, graphite with a soft carbon-like structure, and hard and soft carbon-coated mesophase carbon microspheres; the mass ratio of the second layer of negative electrode active material, conductive agent, and adhesive is 92.6:3.8:3.6, the solid content of the second layer of negative electrode slurry is 30% to 45%, and the viscosity of the second layer of negative electrode slurry is 2000mPa·s to 4000mPa·s; the conductive agent is one or more of conductive carbon black, superconducting carbon black, graphene, single-walled carbon nanotubes and multi-walled carbon nanotubes; the adhesive is one or more of polyvinylidene fluoride, polyacrylic acid, a mixture of styrene-butadiene rubber emulsion and carboxymethyl cellulose, and a mixture of polyacrylonitrile and polyacrylate; the dispersing solvent is N-methylpyrrolidone and / or deionized water.
5. The method for preparing a double-layer negative electrode and a long-life low-temperature starting power lithium-ion battery according to claim 1, characterized in that: The positive electrode sheet in step 4 is an aluminum foil with a thickness of 12 μm to 20 μm, and the thickness of the positive electrode current collector is 63 μm to 67 μm.
6. The method for preparing a double-layer negative electrode and a long-life low-temperature starting power lithium-ion battery according to claim 1, characterized in that: The negative electrode plate in step five is a copper foil, carbon-coated copper foil, porous copper foil or PET copper foil with a thickness of 6μm to 15μm, the thickness ratio of the first layer of negative electrode coating and the second layer of negative electrode coating is 1:1, and the thickness of the double-layer negative electrode collector is 74μm to 78μm.
7. The method for preparing a double-layer negative electrode and a long-life low-temperature starting power lithium-ion battery according to claim 1, characterized in that: The thickness of the diaphragm in step six is 12 μm to 20 μm, and the diaphragm is a polyimide diaphragm, a porous polymer diaphragm, a polyethylene film, a polypropylene film, a cellulose film, a porous polymer film, an aramid film, a polyvinylidene fluoride-hexafluoropropylene copolymer diaphragm, a non-woven fabric film, an inorganic composite film or an aluminum-plastic film.
8. The method for preparing a double-layer negative electrode and a long-life low-temperature starting power lithium-ion battery according to claim 1, characterized in that: The electrolyte described in step six is prepared by lithium salt and solvent, the concentration of lithium salt in the electrolyte is 1.0 mol / L, the lithium salt is one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium bis(oxalate borate), lithium difluorooxalate borate, lithium bis(fluorosulfonyl imide), lithium bis(trifluoromethylsulfonyl imide), and lithium 4,5-dicyano-2-trifluoromethylimidazole; the solvent is one of ethylene carbonate, propylene carbonate, ethylene carbonate, fluoroethylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, γ-butyrolactone, ethyl acetate, propyl acetate, ethyl propionate, propyl propionate, and vinyl sulfate.
Citation Information
Patent Citations
Preparation method of multi-layer coating pole piece
CN111370649A
Low-temperature lithium ion battery negative electrode and lithium ion battery
CN118156403A